The Path to Green Development: The Impact of a Carbon Emissions Trading Scheme on Enterprises’ Environmental Protection Investments - Lv, Shigong; Lv, Yanying; Gao, Da; Liu, Lulu (Sustainability, 2023)
The Carbon Emissions Trading Scheme (CETS) is an important part of China’s environmental reform agenda, which aims to facilitate the green development of enterprises. Using data from listed companies from 2008 to 2020, this study adopts the CETS as a quasi-natural experiment. This study empirically examines the impact of CETS implementation on corporate environmental protection investment (EPI) and explores the underlying mechanisms using the difference-in-difference (DID) method. The results show that: (1) The implementation of CETS significantly promotes firms’ EPI. A series of robustness tests confirms the findings. (2) This study further analyses the impact mechanism of the CETS in promoting the enterprises’ EPI, which is mainly manifested in an increase in emission costs and enforcement rigidity. (3) The heterogeneity test results show that the CETS has a more significant positive effect on the environmental investment of state-owned, large, and heavily polluting enterprises. The conclusions of this study provide both theoretical support and empirical evidence for the implementation of carbon emissions trading policies.